Canva-Based Interactive Digital Comics on Science Content to Enhance Elementary School Students' Learning Outcomes - Sugiantara, I Komang; Kadek Yudiana; I Made Hendra Sukmayasa (Universitas Pendidikan Ganesha, 2024)
This research aims to develop Canva-based digital interactive comic media in science learning, especially on the topic of energy sources, in order to improve the learning outcomes of third grade elementary school students. This research was conducted because the learning process was less effective because the teacher only used the lecture method during learning. Lack of application of effective learning media to support the learning process. This development uses the ADDIE development model. Based on the validity of digital interactive comic media, using two material experts and two learning design experts. The media expert test obtained an average value of 0.95 which is classified as high validity, the material expert test obtained an average value of 0.94 which is classified as high validity, and the learning design expert test obtained an average value of 0.90 which is also classified as high validity. The results of the practicality test for practitioners or teachers obtained a score of 92%, which means the percentage level is very good, the student response to 17 class III students obtained a score of 88.78%, which means a good percentage level, the small group test got a score of 90.46%, which means the percentage level is very good, and the individual test got a score of 93.33%, which means the percentage level is very good and practical to use. The effectiveness test carried out in class III of SD Negeri 1 Ambengan, totaling 17 students, through the resistance t-test obtained a significant value (Sig. 2-tailed) of 0.001. These results show a significant magnitude smaller than 0.05. Based on these results, it was concluded that Canva-based digital interactive comics were proven to be valid, feasible and effective in improving elementary school students' science learning outcomes.